Popular Culture and National Identity - Molina, Rafael Cuevas (2019)
The present essay raises considerations for a “de-Sacralising” approach to the founding myths of contemporary  nationalities, identifying the class interests following them, the contradictions hidden behind the rhetoric and moreover, showing the processes through which those identities were constructed in given historical circumstances.